The American highway the history and culture of roads in the United States - Kaszynski, William (McFarland, 2000)
Minnesota-based writer and photographer Kazynski traces the transformation of the US from a network of places connected by rutted wagon trails to a maze of highways connected to other highways. He describes and illustrates road and bridge construction and the new roadside culture that threw up motels, restaurants, gas stations, and scenic perspectives.